Hak Imunitas Anggota DPR RI Sebagai Pejabat Publik dalam Hal Menjalankan Tugas dan Wewenangnya - Faisal Akbar Nasution (Universitas Medan Area, 2021)
The idea of democracy demands that every form of law and various decisions be approved by the representatives of the people and perhaps consider the interests of the people. Authorization, a law is in the hands of the DPR together with the President and does not involve the holders of sovereignty, namely the people in the process of ordering it, but currently the role and the people in influencing policies to produce a law and to assess the validity of a law laws cannot be underestimated. The research aims to provide immunity rights for members of the DPR RI as public officials in carrying out their duties and authorities. The research method used in this research is normative juridical legal research using an invited approach and the doctrine applied to a legal problem and is prescriptive in nature which is expected to be applied in society. The results of the study concluded that in carrying out their duties and authorities, members of the DPR RI need to be properly and respectably protected with their level of honor as people's representatives who have been elected by the people and each member of the DPR RI must also reflect respectable and foremost personal and behavior in law enforcement